A review of the Diplazontinae of Mongolia (Hymenoptera: Ichneumonidae) - Klopfstein, Seraina (Zootaxa, 2011)
The Diplazontinae identified and described by Setsuya Momoi in the collection of Dr. Kaszab from Mongolia were examined at the Hungarian Natural History Museum in Budapest. Because of insufficient labelling, the type status of some specimens had to be clarified and four lectotypes were designated. Syrphophilus stibarus Momoi,1973 is conspecific with Syrphophilus dilleriator Aubert, 1976, syn. nov., and Syrphoctonus lipothrix (Momoi, 1973) is a junior synonym of Syrphoctonus haemorrhoidalis (Szépligeti, 1898), syn. nov. Diplazon multicolor (Gravenhorst, 1829) is removed from synonymy with Diplazon annulatus (Gravenhorst, 1829), stat. rev. A new species is described, Sussaba mongolica sp. nov., and the male of Syrphoctonus venustus (Dasch, 1964) is re-described to account for the material from Mongolia. The ultrastructure of the tyloids of three species is illustrated by scanning electron micrographs to demonstrate their large variability in the subfamily. Seven species are recorded for the first time from Mongolia, four of which are recorded for the first time from the Eastern Palaearctic. These data on the Mongolian diplazontines provide further evidence for an unusually large proportion of species of this subfamily with a multiregional distribution.